Prescribing pattern in a pediatric out-patient department in Gujarat - Nazima Yunus Mirza; Sagun Desai; Barna Ganguly (Bangladesh Pharmacological Society, 2009)
This study was carried out to find the medicine-prescribing pattern in children taking treatment in pediatric out-patient department of a tertiary care teaching hospital in rural Gujarat. Prescriptions of 606 patients were collected over a period of six months and analyzed for (i) average number of medicines per prescription, (ii) percentage of medicines prescribed by official names, (iii) essentiality status of medicines, (iv) appropriateness of medicines used and (v) cost of prescription. The average number of medicines per prescription was 3.72 ± 0.07 and 46.7% patients were prescribed up to 3 medicines. Of the 1483 medicines prescribed, 456 (30.7%) were prescribed by official names and 77.61% were essential. Only 20.13% prescriptions could be reckoned as most appropriate. Twenty percent of the total cost was on account of non-essential medicines, of which 95% was contributed by non-essential fixed dose drug combinations.